Promoter-proximal pausing by RNA polymerase II in vitro: transcripts shorter than 20 nucleotides are not capped. - Coppola, J A (1983)
We have synthesized RNA from cloned adenovirus 2 late promoter DNA in an in vitro transcription extract under UTP-limiting conditions. Under these circumstances, almost all of the alpha-amanitin-sensitive RNA produced is shorter than 20 nucleotides; most of these short transcripts are present in four species, 6, 7, 13, and 17 nucleotides. These short RNAs are initiated at the adenovirus 2 promoter, as judged by partial sequence analysis and by the abolition of their synthesis upon cleavage of the template DNA at sites which also abolish the production of full-length transcripts. All of the short transcripts can be chased, with excess UTP, into 197-base run-off transcripts; thus, these RNAs are precursors of full-length transcripts and not synthetic "dead ends." Significantly, none of these short RNAs is capped or 2'-O-methylated. However, 79-base run-off transcripts synthesized from this promoter with nonlimiting NTP levels are fully capped.